Between the lines interpreting welfare rights - Melnick, R. Shep 1951- (Brookings Institution, 1994)
Judicial interpretation of federal statutes has often been at the center of political controversy in recent years. In fact, it would be difficult to find a domestic policy area in which statutory interpretation by the federal courts has not played a significant role in shaping the activities of government. In most important cases, judges base their interpretation not on the letter of the law but on their reading of its history, purpose, and spirit.